The Influence of Training Programs, Self-Efficacy, and Work Motivation on the Performance of Indonesian National Police Officers: An Empirical Study at the South Tangerang Police Resort - Paringsih Paringsih; Widodo Sunaryo; Nancy Yusnita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The performance of police officers is a crucial factor in ensuring effective law enforcement and public service delivery. In modern policing environments, organizational support and individual psychological factors are considered important elements that shape officers’ professional behavior and work outcomes. This study aims to examine the influence of training programs, self-efficacy, and work motivation on the performance of Indonesian National Police officers at the South Tangerang Police Resort. The research employed a quantitative approach using a survey design. Data were collected from 136 police officers through structured questionnaires and analyzed using multiple linear regression analysis. The findings indicate that training programs and work motivation are associated with police officers’ performance, while self-efficacy shows a positive but less prominent relationship within the model. These results suggest that organizational initiatives such as structured training programs and supportive motivational environments play an important role in shaping professional performance among police officers. Overall, the study highlights the importance of integrating organizational development strategies and psychological factors to support effective policing practices.